(untitled) (Medico Legal Update, 2020)
Background: Juveniles of today will become the adults of tomorrow, the face of the world. Hence, it is of utmost importance to make sure that the youth of nation are given a wholesome protected environment to thrive and grow in. Aim of the Study: Our study was focussed on retrospectively studying the type of offence committed by the juveniles in the reformatory schools. Material & Method Both male and female inmates of the reformatory schools were studied for the unlawful acts which landed them into the Reformatory schools. Observation & Results: The percentage of boys and girls involved in non-heinous and other offences was 36.5% and 33.3% respectively; but this association of type of offence with gender was found to be statistically non-significant (p>0.05).There were 103 cases of sexual offences, maximum Cases were of POCSO. Conclusion: Comprehensive violence prevention plans in all spheres of life, i.e. homes, schools, communities to reduce and prevent juvenile delinquency. Special programmes should be designed to prevent sexual reoffending among these juveniles. Development of facilities for counselling and psychological and psychiatric treatment as well as introduction of Juvenile mentoring programs is highly recommended in reformatory schools.